TOTAL OF LACTOBACILLUS BIFIDUS IN BREASTFED INFANTS FROM NURSING MOTHERS INTERVENED WITH ZINC - Verawati Parmah; Wardihan Sinrang; Suryani As’ad; Muh. Nasrum Massi; Mardiana Ahmad; Andi Nilawati Usman (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: In pregnancy and nursing, zinc plays an important role, including fetal development and milk secretion. Zinc in the lactation process is a crucial modulator of the mammary gland, which is very important for successful lactation. Objectives: The purpose of this study was to analyze the total of Lactobacillus Bifidus using Quantitative RT-PCR in the feces of breastfed infants from mothers who were given zinc tablets. Methods: This type of research was experimental using a quasi-experimental post-test only with a control design and a quantitative approach. This research was carried out at Antang Perumnas Public Health Center, Kassi-Kassi Health Center, Jumpanang Baru Health Center and Bara-Barayya Health center from March 22 to June 22, 2021. The Population in this study were all newborns from mother with normal zinc levels in 2021 in the Makassar City Health Center area as many as 62 people. The sampling technique used purposive sampling, about 12 samples per group. To avoid dropout and increase power, the sample was then added with an estimated drop out of about 30%, 12 + (30% x 12) = 15.6, rounded up to 16. Each group consisted of 16 samples for breastfed infants from mothers who obtained zinc tablets (intervention) and 16 samples for breastfed infants from mothers who did not obtain zinc tablets (control). This study uses an Independent Sample Test. Results: This study showed that the group of breastfed infants from mothers obtaining zinc tablets had a higher mean value of 2947625215.62 compared to the control group of 162374516.97. There was a difference in the number of Lactobacillus in the intervention group after being treated with a statistically significant difference in the mean of –2785250698.65 by the Independent sample test analysis, the value of p = 0.009 (α < 0.05), which means there was a significant difference between the intervention groups and control group. Conclusion: The highest number of Lactobacillus was the intervention group which indicated a difference of Lactobacillus in the feces of breastfed infants from mothers who obtained zinc tablets.